Pengaruh Intellectual Capital Terhadap Nilai Perusahaan Dengan Managerial Ownership Sebagai Variabel Moderating (Studi pada Sektor Manufaktur yang Listing di BEI Tahun 2013-2017) - Hikmat, Imat; Akhmadi, Akhmadi; Purwanda, Eka (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2019)
This study aims to determine the effect of intellectual capital on company value with managerial ownership as a moderating variable in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2017. By using the Pulic’s-Value Added Intellectual Coefficients (VAIC) Model, this study examines the relationship between intellectual capital (VAIC) to firm value (PBV) and managerial ownership (MO) as a moderating variable. This study’s population is manufacturing companies listed on the Indonesia Stock Exchange (IDX). Based on the purposive sampling method, the sample used was 9 companies. The analytical method used is Moderated Regression Analysis (MRA). Hypothesis testing uses t statistics to test the effect of variables partially with a level of significance of 5%. In addition, a classic assumption test was carried out which included normality test, multicollinearity test, heterocedasticity test, and autocorrelation test. The results of this study indicate that intellectual capital has a significant effect on the positive direction of firm value. This study also proves that there is no significant effect of managerial ownership in the relationship between intellectual capital and firm value